2023
DOI: 10.3389/fpls.2023.1145137
|View full text |Cite
|
Sign up to set email alerts
|

The role of soil temperature in mediterranean vineyards in a climate change context

Abstract: The wine sector faces important challenges related to sustainability issues and the impact of climate change. More frequent extreme climate conditions (high temperatures coupled with severe drought periods) have become a matter of concern for the wine sector of typically dry and warm regions, such as the Mediterranean European countries. Soil is a natural resource crucial to sustaining the equilibrium of ecosystems, economic growth and people’s prosperity worldwide. In viticulture, soils have a great influence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 179 publications
(314 reference statements)
0
11
0
Order By: Relevance
“…The soil temperature recorded in both the upper and lower soil layers, as it was expected, increased in July respect to March and May (Costa et al 2023). It is a factor that depended on the physical soil properties, it has been reported that higher amplitude of the daily temperature has been related to the sand and clay composition in the soil (Krapez et al 2012;Sremac et al 2021).…”
Section: Temperature and Humidity Of Soilmentioning
confidence: 67%
“…The soil temperature recorded in both the upper and lower soil layers, as it was expected, increased in July respect to March and May (Costa et al 2023). It is a factor that depended on the physical soil properties, it has been reported that higher amplitude of the daily temperature has been related to the sand and clay composition in the soil (Krapez et al 2012;Sremac et al 2021).…”
Section: Temperature and Humidity Of Soilmentioning
confidence: 67%
“…This study focused on the effects of two fertilizer programs-organo-mineral and chemical-on under-vine TSR in a vineyard because it has been recognized that TSR values in under-rows are higher than those in inter-rows in a vineyard [26]. In addition, TSR is an indicator of overall biological activity and a descriptor of soil quality that is strongly linked to agricultural soil management practices, such as tillage and irrigation, but also to abiotic factors (e.g., temperature and moisture) and chemical and physical soil traits [26,47,48]. The soil of the tested vineyard could be classified as clay-loam soil and poor in terms of SOC, and in fact, all the soil profiles could be characterized by very low SOM values (optimal values are between 2 and 3%) [49][50][51], which underlined low fertility conditions.…”
Section: Discussionmentioning
confidence: 99%
“…To optimize the utilization of available solar radiation and facilitate vineyard management, grapevines are typically arranged in rows. This configuration results in a low canopy profile, which significantly increases the portion of soil directly exposed to evaporation (Costa et al, 2019;Costa et al, 2023). As the grapevines reach their maximum vegetative growth during the veraison stage, soil water availability rapidly diminishes, thus requiring irrigation intervention.…”
Section: Biophysical Model Proposal To Predict Canopy Conductance To ...mentioning
confidence: 99%